2012
DOI: 10.1073/pnas.1203954109
|View full text |Cite
|
Sign up to set email alerts
|

Mouse model recapitulating human Fcγ receptor structural and functional diversity

Abstract: The in vivo biological activities of IgG antibodies result from their bifunctional nature, in which antigen recognition by the Fab is coupled to the effector and immunomodulatory diversity found in the Fc domain. This diversity, resulting from both amino acid and glycan heterogeneity, is translated into cellular responses through Fcγ receptors (FcγRs), a structurally and functionally diverse family of cell surface receptors found throughout the immune system. Although many of the overall features of this syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
337
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 265 publications
(355 citation statements)
references
References 25 publications
17
337
1
Order By: Relevance
“…The next steps for dengue research could explore the role of FcgRIIa and FcgRIIb in human infections to further the understanding of signaling mechanisms and routing pathways mediated by engagement of DENV immune complexes and to study the effects of different viral serotypes complexed with different human or mouse IgG subclasses. Finally, these results support the development of a mouse model wherein all murine FcgRs are replaced with human FcgRs (31). The addition of FcgRIIa-expressing cells into mice could counterbalance the unopposed inhibitory murine FcgRIIb isoform, enable ADE, and generate a much needed small animal model to advance our understanding of complicated dengue disease.…”
Section: Discussionmentioning
confidence: 63%
“…The next steps for dengue research could explore the role of FcgRIIa and FcgRIIb in human infections to further the understanding of signaling mechanisms and routing pathways mediated by engagement of DENV immune complexes and to study the effects of different viral serotypes complexed with different human or mouse IgG subclasses. Finally, these results support the development of a mouse model wherein all murine FcgRs are replaced with human FcgRs (31). The addition of FcgRIIa-expressing cells into mice could counterbalance the unopposed inhibitory murine FcgRIIb isoform, enable ADE, and generate a much needed small animal model to advance our understanding of complicated dengue disease.…”
Section: Discussionmentioning
confidence: 63%
“…However, the advent of fully humanized FcgR mice on a non-immune compromised mouse background may provide an acceptable model system. 51 An additional consideration for macrophage-mediated ADCR concerns the context in which the antibody Fc is presented to the macrophage. It was previously demonstrated that IL-10 was not elicited from macrophages when an IgG1 mAb was coated directly onto plates.…”
Section: Discussionmentioning
confidence: 99%
“…To test the in vivo potency of these engineered chimeric antibodies, we used a novel B6 mouse strain in which the mouse Fcgr2b gene was deleted and the human FCGR2B (huFCGR2B) gene was inserted as a transgene. The huFCGR2B gene, driven by its human promoter elements, retains the specific cellular expression pattern seen in the human and is functional for FcγRIIB inhibitory and immunomodulatory activities (38).…”
Section: Fc-engineered Anti-dr5 Antibody With Enhanced Fcγriib Bindinmentioning
confidence: 99%